2022
DOI: 10.1101/2022.04.05.22273358
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Built environment’s impact on COVID-19 transmission and mental health revealed by COVID-19 Participant Experience data from the All of Us Research Program

Abstract: Objectives: The coronavirus disease 2019 (COVID-19) pandemic has led to millions of deaths. Effectively cutting the transmission of COVID-19 is essential to reduce the impact. Previous studies have observed the potential relationship between the built environment and COVID-19 transmission, however, to date, stringent studies investigating these relationships at the individual level are still insufficient. Here, we aim to examine the relationship between household types and COVID-19 infection (or mental health)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The difference in mortality between different geographical locations also indicates that in addition to societal/behavioral factors, genetic and environmental differences may influence host defense against SARS-CoV-2 infection [ 5 ]. A recent study of All of Us participants showed that built environment of houses with a shared component increased the rate of SARS-CoV-2 transmission [ 6 ]. However, the elderly and individuals with underlying diseases or low immune function are more likely to develop severe COVID-19 [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The difference in mortality between different geographical locations also indicates that in addition to societal/behavioral factors, genetic and environmental differences may influence host defense against SARS-CoV-2 infection [ 5 ]. A recent study of All of Us participants showed that built environment of houses with a shared component increased the rate of SARS-CoV-2 transmission [ 6 ]. However, the elderly and individuals with underlying diseases or low immune function are more likely to develop severe COVID-19 [ 7 ].…”
Section: Introductionmentioning
confidence: 99%